2017
DOI: 10.3390/ijms18020466
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Pattern, Flux, and Function of Autophagy in Spinal Cord Injury

Abstract: Previous studies have indicated that autophagy plays a critical role in spinal cord injury (SCI), including traumatic spinal cord injury (TSCI) and ischemia-reperfusion spinal cord injury (IRSCI). However, while the understanding of mechanisms underlying autophagy in SCI has progressed, there remain several controversial points: (1) temporal pattern results of autophagic activation after SCI are not consistent across studies; (2) effect of accumulation of autophagosomes due to the blockade or enhancement of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 110 publications
0
44
0
Order By: Relevance
“…Previous studies employing spinal cord contusion injury model have shown that levels of LC3 and Beclin 1 were increased and peaked at 7 or 10 days after injury, while studies employing hemi‐section injury model showed that the increase in LC3 signals was detected as early as 4 hours and peaked at 3 days after hemi‐section injury. The inconsistency of temporal pattern of autophagy following SCI could be prompted by the difference in SCI models or injury severity. Under our experimental condition, autophagic activity was significantly enhanced after SCI, peaked at 3 days, and fell slightly at 7 days after injury.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies employing spinal cord contusion injury model have shown that levels of LC3 and Beclin 1 were increased and peaked at 7 or 10 days after injury, while studies employing hemi‐section injury model showed that the increase in LC3 signals was detected as early as 4 hours and peaked at 3 days after hemi‐section injury. The inconsistency of temporal pattern of autophagy following SCI could be prompted by the difference in SCI models or injury severity. Under our experimental condition, autophagic activity was significantly enhanced after SCI, peaked at 3 days, and fell slightly at 7 days after injury.…”
Section: Discussionmentioning
confidence: 52%
“…The primary injury, which is irreversible, means that the spinal cord is injured by a direct or indirect violence. However, the secondary injury, following the primary injury, causes a sustained injury at the molecular and cellular level surrounding the epicenter of the lesion, including edema, hemorrhage, apoptosis, inflammation and oxidative stress, significantly affecting the prognosis of SCI [ 3 5 ]. It is considered as an effective method to treat SCI by reducing the secondary injury.…”
Section: Introductionmentioning
confidence: 99%
“…The term “autophagic flux” describe that autophagy is a dynamic process (Zhou et al, 2017 ), and there is a dynamic equilibrium between autophagosome formation and clearance by lysosome. Actually, the rate at which material is cleared from the cell by autophagy is known as autophagy flux (Palumbo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%